2022
DOI: 10.48550/arxiv.2203.06845
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lower bounds for negative moments of quadratic Dirichlet $L$-functions

Abstract: We establish lower bounds for the 2k-th moment of families of quadratic Dirichlet L-functions at the central point for all real k < 0, assuming a conjecture of S. Chowla on the non-vanishing of these L-values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In [7], asymptotic formulas are achieved for these negative moments for certain ranges of the shifts over function fields. Additionally, lower bounds are given in [9] for negative moments of families of quadratic Dirichlet L-functions at the central point in the number field setting, assuming the truth of a conjecture of S. Chowla [6] on the non-vanishing of these L-values. Note that the results in [9] are only expected to be sharp for the 2k-th moment with −5/2 ≤ k < 0 since the work in [8] also suggests certain phase changes in the asymptotic formulas for the 2k-th moment of the family of quadratic Dirichlet L-functions when 2k = −(2j + 1/2) for any positive integer j.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [7], asymptotic formulas are achieved for these negative moments for certain ranges of the shifts over function fields. Additionally, lower bounds are given in [9] for negative moments of families of quadratic Dirichlet L-functions at the central point in the number field setting, assuming the truth of a conjecture of S. Chowla [6] on the non-vanishing of these L-values. Note that the results in [9] are only expected to be sharp for the 2k-th moment with −5/2 ≤ k < 0 since the work in [8] also suggests certain phase changes in the asymptotic formulas for the 2k-th moment of the family of quadratic Dirichlet L-functions when 2k = −(2j + 1/2) for any positive integer j.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, lower bounds are given in [9] for negative moments of families of quadratic Dirichlet L-functions at the central point in the number field setting, assuming the truth of a conjecture of S. Chowla [6] on the non-vanishing of these L-values. Note that the results in [9] are only expected to be sharp for the 2k-th moment with −5/2 ≤ k < 0 since the work in [8] also suggests certain phase changes in the asymptotic formulas for the 2k-th moment of the family of quadratic Dirichlet L-functions when 2k = −(2j + 1/2) for any positive integer j. We also point out here that asymptotic formulas for negative moments of the above family of L-functions at 1 were obtained by A. Granville and K. Soundararajan [11] in the number field setting and by A. Lumley [14] for function fields.…”
Section: Introductionmentioning
confidence: 99%
“…According to a conjecture by S. Chowla [16] in his work on the quadratic Dirichlet L-functions, it is suggested that L( 1 2 , χ) should not equal to zero for all primitive real Dirichlet characters χ. Assuming S. Chowla's conjecture, Peng Gao [5] establishes lower bounds for the 2k-th moment of quadratic Dirichlet L-functions for all real k < 0. The estimation is given by…”
Section: Introductionmentioning
confidence: 99%